Penentuan Episenter dan Hiposenter dengan Menggunakan Metode Wadati dan Lingkaran - Wira Hadi Kusuma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Seismic waves propagate from the earthquake source in all directions, with a spherical pattern moving within a three-dimensional field. Therefore, a seismograph is designed to record vibration components in both vertical and horizontal directions. Vertical vibrations are recorded on the vertical component seismogram or UD (up-down or compression-dilatation), while horizontal vibrations are recorded on the N–S (north-south) and E–W (east-west) component seismograms. These three components can be used to analyze wave propagation in three-dimensional directions. Earthquakes can be observed through the arrival of P-waves and S-waves on a seismogram. The arrival times of P-waves and S-waves are used to determine the hypocenter, which is the earthquake focus within the Earth, and the epicenter, which is the projection of the hypocenter onto the Earth’s surface. Various methods are available to determine the epicenter and hypocenter; in this study, the two- to three-station circle method and the Wadati method were used to determine the earthquake’s epicenter and hypocenter based on picking results from Seisgram2K70.